A rare case of bilateral complex wrist injury in a professional motocross rider - Pedrazzini, Alessio; Tocco, Silvio; Vaienti, Enrico; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2016)
We describe the treatment of a 29 year-old professional motocross rider, who sustained a perilunate dislocation in his right wrist and a distal radius fracture and dorsal dislocation of his left wrist during a race. Both wrists were treated acutely during a single operating session. Surgery consisted in open reduction, k-wire fixation and mini-anchor repair of the scapho-lunate and luno-triquetrium ligaments on the right wrist, while closed reduction and percutaneous k-wire fixation was used in the left wrist. Follow-up at 6 months has shown satisfying radiological and functional outcomes in both wrists. The rider ultimately returned to motocross 5 months following surgery